Pre-Solutrean rock art in southernmost Europe: Evidence from Las Ventanas Cave (Andalusia, Spain) - Cortés Sánchez, Miguel (2018)
The south of Iberia conserves an important group of Palaeolithic rock art sites. The graph isms have been mostly attributed to the Solutrean and Magdalenian periods, while the possibility that older remains exist has provoked extensive debate. This circumstance has been linked to both the cited periods, until recently, due to the transition from the Middle to Upper Palaeolithic in the extreme southwest of Europe as well as the non-existence of some of the early periods of Palaeolithic art documented in northern Iberia. This study presents the results of interdisciplinary research conducted in Las Ventanas Cave. These results enabled us to identify a new Palaeolithic rock art site. The technical, stylistic and temporal traits point to certain similarities with the range of exterior deep engravings in Cantabrian Palaeolithic rock art. Ventanas appears to corroborate the age attributed to those kinds of graphic expression and points to the early arrival of the Upper Palaeolithic in the south of Iberia. Importantly, the results provide information on the pre-Solutrean date attributed to trilinear hind figures. These findings challenge the supposed Neanderthal survival idea at one of the main late Middle Palaeolithic southern Iberian sites (Cariguela) and, due to the parallels between them and an engraving attributed to this period in Gibraltar, it raises the possibility of interaction between modern humans and Neanderthals in the extreme southwest of Europe.